Effects of Kinesio Taping ® on range of motion and shoulder pain relief in mastectomy patients. - Rêgo, Ludmila Martins de França; Revoredo, Myrza Maria Paiva; Basilio, Franciane Batista; Silva, Rodrigo Marcel Valentim da; Lins, Caio Alano de Almeida (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Owing to the surgery of breast cancer, post-surgery healing can evolve with functional alterations, such as pain, decreasing of movement breadth and other alterations that can occur on the homolateral shoulder of surgery. Within this prospect, one proposes the Kinesio Taping ® method as a new resource in physiotherapy area that might be used as coadjuvant treatment of mastectomized patients. Objective: Analysis of the effect of Kinesio Taping ® method in relation with pain relief and increase of the breadth of homolateral shoulder movement from mastectomized patients. Method: Bibliographic review was fulfilled from data bases such as LILACS, PubMed, SciELO, MEDLINE, academic Google, besides other sites and books. Researched period ranged from 2000 to 2014. Results: The results of the researched works indicate that Kinesio taping ® method is effective in the treatment of algic complaints and of increase of movement breadth in pathologies like tendinitis at the rotator cuff and syndrome of shoulder impact. None of the cited studies were realized in mastectomized patients. Conclusion: The mechanisms wherein functional bandage could aid over shoulder performance of mactetomized patients are not clear because there are not any study that proves the effectiveness of Kinesio Taping ® method over this type of treatment to the date.